(3QSGdI aj GdhLhg GdJj Hjf BNQ ShQI aUdJ hHjf Chd ShQI GdThQis - (3GdYLdhfj GdebQF, HOQ GdOjf, MSfs ((3eMeO Hf eMeO Hf jhSa GdNGdOjs)
(3ChdgG (B:s
(3HYO GdHSedI hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hHYO abO SCd SjOfG GdTjN MSf GdebQF GdYLdhfj GdeTGQ Edjg HYV CUMGHg Cf jYed GdhLhg GdJj Hjf BNQ ShQI aUdJ hHjf Chd ShQI (B((3GdThQi (B) (3hePGgH GdbQGA ajgeGs
(3BNQgG (B:s
(3aLedI eG ddbQGA ef GdhLhg aj gPG cdg hGKfGf hSJhf hLgG Shi MaU adg SHY hYTQhf hLgG aJUjQ GdLedI KdGK eGFI hJSYI hKeGfhf hLgG hGddg CYdes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs